Physico-Chemical and Morphogenetic Characteristics of Petrogypsids
Physico-chemical and morphogenetic characteristics of the gypsiferous soils have been studied in the arid region of Rajasthan. Detailed survey of the gypsiferous area has been carried out to characterize the constraints for their sustainable management. The study site was located near village Kawas. 20 km .. south of Banner, where the Petrogypsids occur widely. Detailed soil s,l